Cognitive Networked Sensing and Big Data - Qiu, Robert; Wicks, Michael (Springer New York : Imprint: Springer, 2014)
Cognitive Networked Sensing and Big Data defines high-dimensional data processing in the context of wireless distributed computing and cognitive sensing. This book presents the challenges that are unique to this area such as synchronization caused by the high mobility of the nodes. The authors discuss the integration of software defined radio implementation and testbed development. The book also bridges new research results and contextual reviews. Additionally, the authors provide an examination of large cognitive radio network; hardware testbed; distributed sensing; and distributed computing.